Evaluation of Sarbagita Urban Infrastructure Cooperation in Public Service Management - I Gede Wyana Lokantara (Journal of Architectural Research and Design Studies)
Sarbagita area refers to a system of cities in South Bali Region consisting of several cities namely Denpasar City, some parts of Badung regency, Gianyar regency, and Tabanan regency. Urban Area of Sarbagita becomes a form of agglomeration of Denpasar City with other cities developed through regionalization process, i.e. metropolitan cooperation. This leads to an externality that requires the integrated handling of each region in the metropolitan area of Sarbagita through a co-operative institution. The purpose of this study is to analyse the implementation and the form of Sarbagita cooperation, and to evaluate the performance of the cooperation of the Sarbagita urban areas in the delivery of public services and tourism activities. Thus, the level of success of the program and the way to do the cooperation can be measured. This research uses deductive approach with qualitative and quantitative mixed method approach. Qualitative descriptive analysis was conducted to know the condition before and after Sarbagita cooperation performance and quantitative analysis was used to give scoring to cooperation performance. The results of this study are (1) Based on the results of the analysis, Sarbagita area cooperation used a collaborative planning system, that is running the program with the working mechanism of the combining regulations between local intergovernmental agreement for the common interest and then by holding a joint meeting in decision-making as reflected in written Agreements to establish cooperation programs. The characteristic of this cooperation is to set up a centralized operational body consisting of elected representatives who are assigned to join it. (2) Overall, Sarbagita area cooperation is still experiencing some constraints in the implementation process. The evaluation criteria of effectiveness and efficiency has not been optimal so that the result of assessment criteria of Sarbagita cooperation program can be categorized in the level of medium.